Smart Vehicle Solution Kit for Advanced Driving Assistance - Dutta, Koustav; Prasad, Rajendra (International Journal of Computer Sciences and Engineering, 2019)
The following paper presents a noble model for solving the problems faced by the drivers while driving and thus provides them with advanced driving assistance. The solution demonstrated by our designed project is helpful in saving the lives of vehicle occupants. Automation is a key to solve day to day issues and reducing the complexities. The paper provides the solution for the major problems faced by the driver on road and also helping them in case of an accidents. The paper provides the information regarding the entire design of the automated system and its role in saving the lives and its broader aspects.